Urgensi Motivasi Belajar terhadap Keberhasilan Menuntut Ilmu Perspektif Kitab Ta’lim Muta’allim - Himmatul Ulya; Abdul Muhid (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2021)
The book of Ta’lim Muta’allim is the opus of Sheikh Tajuddin Nu'man bin Ibrahim bin al-Khalil al-Zarnuji or commonly known as Sheikh Al-Zarnuji. A phenomenal book about the concept of Islamic education. Not a few writings that examine the contents of the book from another point of view. However, in this article the focus aims to explain more deeply about the theme of learning motivation contained in the Ta’lim Muta’allim book, precisely on the 5th theme or chapter entitled sincerity, perseverance and aspirations by using the literature review method. The findings of this study indicate that sincerity, perseverance and noble ideals are closely related and mutually supportive. To achieve success in studying, students must have lofty ideals, show great will or motivation and serious effort. Willingness without effort will not maximize the results, and vice versa. In this case, what is meant by the will is motivation, while the effort in question is persistence or continuity in learning.